Processo de desenvolvimento da imaginação na pré-escola: implicações de um programa de intervenção ludo-pedagógico a partir do gênero musical samba - Bezerra, Janaína Pereira Duarte [UNESP] (2015)
This research aimed at understanding the development process of psychological function higher imagination of children of preschool age from the implications of a Ludo-educational intervention program built and developed on the premises of CCI (Children Living Center) FCT / UNESP - Presidente Prudente / SP. For this purpose, takes over as theoretical and methodological reference the Historical and Dialectical Materialism to Historical and Cultural Theory, which provides a differentiated understanding of the human development process. Held with a group of fifteen (15) children in preschool, where 10 (ten) of these children were considered research participants subject since they were the most frequent and more participatory, interventions they conducted up from 16 (sixteen ) meetings, and the activities are structured considering the genre samba as the main content to be transmitted to the research subjects with a view to understanding the development process of psychological function greater imagination. The subjects of the research participants were able to experience social and learning situations, times when it was possible to identify the passage of most basic thoughts to more complex ways of thinking that engendered the construction of imaginative processes more elaborate of the subjects. Certainly this research contributed to the improvement of teachers' work, as well as in the scientific understanding of children's imagination development process in the School of Early Childhood Education